Kriegserfahrungen erzählen : Geschichts- und literaturwissenschaftliche Perspektiven - Rogge, Jörg (2017)
How were accounts of war told in the Middle Ages and the Early Modern era? The contributions to this volume pursue this question in an innovative way through the combination of historical and literary methodologies. With the aid of this interdisciplinary approach, the texts examine storytelling practices and strategies which dissolved genre barriers between factual and fictional texts, thereby expanding insights with regard to their presentation of experience. This volume is not only a pioneering work of cultural studies research, but also an example of successful and productive interdisciplinary collaboration.